Fracture analysis of girth welded pipelines with 3D embedded cracks subjected to biaxial loading conditions - Yi, Dake. (2013)
Steel pipelines used for oil and gas transportation are joined by girth welding and welds may contain weld imperfections/defects such as lack of fusion, under-cuts, porosity, slag inclusion etc. of certain height and length at certain location along the longitudinal direction of the weld. During the installation and operation, these pipelines are exposed to large plastic deformation. Fracture assessment procedures: BS7910:2005 [1] or R6 [2], are not suitable for such plastic strains (3%). The evolution of crack tip opening displacement (CTOD) of the pipeline with elliptical embedded crack in a girth weld is investigated under biaxial loading conditions using a three dimensional elastic–plastic finite element method. Based on the results, empirical formulas depicting relationship between the CTOD and the global strain are proposed.